2008
DOI: 10.1016/j.jad.2007.12.228
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids and supportive psychotherapy for perinatal depression: A randomized placebo-controlled study

Abstract: Background-Perinatal major depressive disorder (MDD), including antenatal and postpartum depression, is common and has serious consequences. This study was designed to investigate the feasibility, safety, and efficacy of omega-3 fatty acids for perinatal depression in addition to supportive psychotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
136
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 43 publications
(34 reference statements)
4
136
0
5
Order By: Relevance
“…105 It has been reported that fish consumption and omega-3 status after childbirth are not associated with PND, 106 but there is still interest in exploring the role of omega-3 fatty acids in PND, alone or combined with supportive psychotherapy. 107 …”
Section: Pharmacological Interventions or Supplementsmentioning
confidence: 99%
“…105 It has been reported that fish consumption and omega-3 status after childbirth are not associated with PND, 106 but there is still interest in exploring the role of omega-3 fatty acids in PND, alone or combined with supportive psychotherapy. 107 …”
Section: Pharmacological Interventions or Supplementsmentioning
confidence: 99%
“…Of the former, six were randomized controlled trials (Doornbos et al, 2009;Freeman et al, 2008;Llorent et al, 2003;Makrides et al, 2010;Mozurkewich et al, 2013;Rees, Austin, & Parker, 2008) and two pilot trials (Freeman et al, 2006;Marangell et al, 2004). The nine observational studies included: one ecological study (Hibbeln, 2002), a cross-sectional study (De Vriese, Christophe, & Maes, 2003), a case-control study (Browne, Scott, & Silvers, 2006), and six cohort studies (da Rocha & Kac, 2012;Markhus et al, 2013;Miyake et al, 2006;Otto, De Groot, & Hornstra, 2003;Parker et al, 2014;Str酶m, Mortensen, Halldorsson, Thorsdottir, & Olsen, 2009).…”
Section: Overall Results In Context With Expectations Arising From Thmentioning
confidence: 99%
“…For three studies, depression was not the primary outcome measure (35,36,41) . All included studies used marine-derived n-3 PUFA interventions; some used fish oil (35,36,44) , some DHA (41,43) , and some a combination of DHA and EPA (42,45) . Therefore, the remainder of the present paper focuses on these fatty acids.…”
Section: Resultsmentioning
confidence: 99%